Superior performance of biocomposite nanoparticles PLGA-RES in protecting oocytes against vitrification stimuli - Hai, Guiping; Bai, Jiachen; Liu, Yucheng; Li, Jun; Liu, Aiju; Wang, Jingjing; Liu, Qian; Liu, Weijun; Wan, Pengcheng; Fu, Xiangwei (Frontiers in Bioengineering and Biotechnology, 2024)
Irreversible cryogenic damage caused by oocyte vitrification limits its widespread use in female fertility preservation. In recent years, nanoparticles (NPs) have gained great attention as potential alternatives in protecting oocytes against cryoinjuries. In this paper, a novel composite nanoparticle, poly (lactic-co-glycolic acid)-resveratrol (PLGA-RES) was designed to improve the biocompatibility and sustained release properties by encapsulating natural antioxidant RES into PLGA NPs. Firstly, biotoxicity and oxidation resistance of PLGA-RES were determined, and the results showed that PLGA-RES had nontoxic effect on oocyte survival during in vitro maturation (IVM) (97.08% ± 0.24% vs. 98.89% ± 1.11%, p > 0.05). Notably, PLGA-RES even increased maturation (65.10% ± 4.11% vs. 52.85% ± 2.87%, p < 0.05) and blastocyst rate (56.13% ± 1.36% vs. 40.91% ± 5.85%, p < 0.05). Moreover, the reduced reactive oxygen species (ROS) level (13.49 ± 2.30 vs. 34.07 ± 3.30, p < 0.01), increased glutathione (GSH) (44.13 ± 1.57 vs. 37.62 ± 1.79, p < 0.01) and elevated mitochondrial membrane potential (MMP) levels (43.10 ± 1.81 vs. 28.52 ± 1.25, p < 0.01) were observed in oocytes treated with PLGA-RES when compared with that of the control group. Subsequently, the role of PLGA-RES played in oocytes during vitrification was systematically evaluated. The results showed that the addition of PLGA-RES during vitrification and thawing significantly improved the survival rate (80.42% ± 1.97% vs. 75.37% ± 1.3%, p < 0.05). Meanwhile, increased GSH (15.09 ± 0.86 vs. 14.51 ± 0.78, p < 0.01) and mitochondrial membrane potential (22.56 ± 3.15 vs. 6.79 ± 0.60, p < 0.01), decreased reactive oxygen species levels (52.11 ± 2.95 vs. 75.41 ± 7.23, p < 0.05) and reduced mitochondrial abnormality distribution rate (25.00% ± 0.29% vs. 33.33% ± 1.15%, p < 0.01) were assessed in vitrified MII oocytes treated with PLGA-RES. Furthermore, transcriptomic analyses demonstrated that PLGA-RES participated in endocytosis and PI3K/AKT/mTOR pathway regulation, which was verified by the rescued expression of ARRB2 and ULK3 protein after PLGA-RES treatment. In conclusion, PLGA-RES exhibited potent antioxidant activity, and could be used as an efficacious strategy to improve the quality of vitrified oocytes.